The Effect of SOX Section 404: Costs, Earnings Quality, and Stock Prices - ILIEV, PETER (Journal of Finance, 2010)
ABSTRACT This paper exploits a natural quasi‐experiment to isolate the effects that were uniquely due to the Sarbanes–Oxley Act (SOX): U.S. firms with a public float under $75 million could delay Section 404 compliance, and foreign firms under $700 million could delay the auditor's attestation requirement. As designed, Section 404 led to conservative reported earnings, but also imposed real costs. On net, SOX compliance reduced the market value of small firms.